Decidualized human decidual stromal cells inhibit chemotaxis of activated T cells: a potential mechanism of maternal-fetal immune tolerance - Llorca, Tatiana; Ruiz-Magaña, Maria Jose; Martinez-Aguilar, Rocio; García-Valdeavero, Olga María; Rodríguez-Doña, Lucia; Abadia-Molina, Ana Clara; Ruiz-Ruiz, Carmen; Olivares, Enrique G. (Frontiers in Immunology, 2023)
Background. Numerous lines of evidence confirm that decidual stromal cells (DSCs) play a key role in maternal-fetal immune tolerance. Under the influence of progesterone and other hormones, the DSCs go through a process of differentiation (decidualization) during normal pregnancy. In mice, DSCs inhibit the expression of chemokines that attract abortigenic Th1 and Tc cells to the decidua. We have studied this phenomenon in humans.Methods. We established human DSC lines and decidualized these cells in vitro with progesterone and cAMP. We determined the expression of the chemokines CXCL9, CXCL10 and CXCL11, whose receptor CXCR3 is expressed by Th1 and Tc cells, in undifferentiated DSCs and decidualized DSCs by qRT-PCR. Activated CD3+CXCR3+ cells, including CD4+ Th1 cells and CD8+ Tc cells, were induced in vitro. The migration capacity of these activated lymphocytes was investigated in Transwell chambers with conditioned media from undifferentiated and decidualized DSCs.Results. We demonstrated that CXCL9 was not expressed by DSCs, whereas the expression of CXCL10 and CXCL11 was inhibited in decidualized cells. Conditioned media from decidualized cells significantly inhibited the migration of Th1 and Tc cells. We found that decidualized cells secrete factors of MW less than 6000-8000 Da, which actively inhibit the chemotaxis of these lymphocytes.Discussion. These results confirm in humans that decidualization of DSCs inhibits the expression by these cells of chemokines that attract Th1 and Tc cells and induces the secretion by DSCs of factors that inhibit the chemotaxis of these lymphocytes, thus preventing the arrival of abortigenic T cells in the decidua.